Analisis Risiko Usahatani Nilam di Desa Karya Bhakti Kecamatan Kulisusu Barat Kabupaten Buton Utara - Feronika, Vanti; Bafadal , Azhar; Gusmiarty Abdullah , Weka (Perbal: Jurnal Pertanian Berkelanjutan, 2023)
Patchouli plants have high economic value, but patchouli plants have farming risks faced by farmers. The purpose of this research is to identify the risk at each stage of patchouli farming and to analyze the magnitude of the risk in patchouli farming. The population in this study were all 105 patchouli farmers. Determination of the sample in this study was carried out by simple random sampling totaling 51 farmers using the slovin formula. The variables observed in this study were the characteristics of the respondents: age, education level, number of dependents, land area, and farming experience. Farm risk: risk occurrence, risk frequency, risk source, risk qualitative impact, risk quantitative impact, risk magnitude, and risk classification. The data analysis used in this research is descriptive qualitative. The results of the study indicate that the risks that occur during land processing are that there are no tools and materials and work accidents. At the time of planting the risk that occurs is rotting plants. During maintenance, the risks that occur are aphids, stunted plants, elephantiasis and root rot. At the time of harvesting the risk that occurs is crop failure. The magnitude of the risk during land cultivation is moderate, at the time of planting, the magnitude of the risk is high, during maintenance, the magnitude of the risk is high and at the time of harvesting the magnitude of the risk is moderate.Keywords: farming, patchouli, risk